Vertical asymptotes can be found by setting the denominator equal to 0
x^2-6x = 0
factor out x
x(x-6)
set the two parts equal to 0
x = 0
x-6 = 0
x = 6
so the two x values are 0 and 6
ANSWER: B. x = 0, x = 6
Answer:
B
Step-by-step explanation:
Answer:
x = 1.5
Step-by-step explanation:
First, we distribute (get rid of parentheses):
6x - 3 - 3x = 5 - x - 2
Then, we simplify:
3x - 3 = 3 - x
Then, we combine like terms:
3x + x = 3 + 3
Then, we simplify again:
4x + 6
Finally, we divide 4 on both sides:
We got x = 1.5
Hope this helps!
Answer:
Yes, you can conclude that ΔJKL ≅ XYZ.
Step-by-step explanation:
I forget how to describe it in geometric terms but, if you read the similarity statement again, and follow each angle, you'll notice that the shapes match, and they correspond to each other, it would be different if it said something like ΔLKJ ≅ XYZ because it does not match.
If you're looking for a specific reason, we'd say that they're congruent because of SAS (Side-Angle-Side)
If this still confuses you, hit me up.